The Properties of polymer composites filled with Mg(OH) 2 powder - (:unkn) unknown (My University, 2012)
In this study, a nanomagnesium hydroxide powder and two kinds of micro-Mg(OH) 2 with different particle sizes and ratios, were chosen as fillers and mixed with isotactic polypropylene (¡PP) to form a series of composites by a extrusion and injection processing technique. The results showed that the elasticity modulus, hardness and izod impact strength of composites improved with decreasing particle size. The structure and properties of the composites are characterized using a scanning electron microscopy (SEM) and Energy dispersive X-ray spectroscopy (EDS). Furthermore, PP composites were subjected to examinations to obtain their tensile strengths, yield strengths, elasticity modulus, percent elongation, Izod impact strength, hardness, heat deflection temperature (HDT), Vicat softening point and melt flow index (MFI). © MD Publications Pvt. Ltd.
Keywords: Isotactic polypropylene; Magnesmm hydroxide; Nanocomposites; Particle size